Assessing the Impact of Land Use on Water Quality across Multiple Spatial Scales in U-tapao River Basin, Thailand - Gyawali, S.; Techato, K.; Monprapusson, S. (Journal of Institute of Science and Technology, 2015)
The study investigated the linkages between land uses and water quality in U-tapao river basin, Thailand, in order to examine the impact of land use changes on full -basin, sub-watershed and buffer zone scales (1000m, 500m and 200m) on river water quality through Geographical Information Systems (GIS) and statistical analyses. Correlation and regression analysis were applied for ten water quality parameters. In scale analysis, in the most cases, the sub-watershed scale showed the clear relationship between land use water quality rather than full-basin and buffer zone scales. This indicates that the level of relationship between land use and water quality depends upon scale therefore the relationship between water quality parameters and land uses should be studied in multiple scales and it helps to develop effective river basin management in future. Journal of Institute of Science and Technology, 2015, 20(2): 54-60